Simulações computacionais de escoamentos sobre pás de turbinas eólicas de eixo vertical utilizando em conjunto os métodos pseudoespectral de Fourier e o da fronteira imersa - Monteiro, Lucas Marques (2023)
Changes in climate behavior over the years, accompanied by a strong increase in energy demand by countries around the world, have led authorities and researchers to improve the search for renewable, clean energy sources with low environmental impact. The development of vertical axis wind turbines is an assertive and efficient option, especially in places with low wind speeds and unavailability of large spaces. Then, the present work presents and analyzes the main fluid dynamic aspects related to vertical axis wind turbines. The objective is to investigate and estimate the performance parameters, as well as to evaluate the flow dynamics on these machines. For this, it is proposed to verify the applicability of the IMERSPEC methodology, responsible for numerical and computational modeling of these flows. It is a high-order convergence methodology with low computational cost, when compared to other high-order methodologies, resulting from the coupling of the Fourier pseudospectral method and the immersed boundary method. The imposition of the rotational movement on the turbine blades is guaranteed by a specific subroutine, implemented from a mathematical model, developed and presented in the present work. This subroutine, added to the computational platform together with the IMERSPEC methodology, contemplates the fluid-structure interaction between the turbine and the flow, allowing the estimation of performance coefficients, such as power, torque, normal force, tangential force, lift force and drag force. Initially, to validate the proposed methodology, two-dimensional flow simulations are carried out on a NACA 0012 airfoil for a Reynolds number equal to 1000. From the proposed numerical simulations, convergence and good agreement of the results presented in relation to the reference works are obtained. The behavior of the flow over the airfoil and the different modes of formation of the wakes are evaluated by the fields of velocity, pressure and vorticity, as a function of the angle of attack. Furthemore, to verify the accuracy and potentiality of the IMERSPEC methodology, an analysis is performed, therefore, for fluid dynamic problems in vertical axis turbines, still two-dimensional. The solidity of the turbine is investigated through the simulation of flows over turbines with one and three blades, composed by the airfoil NACA 0015. It also presents the influence of increasing the Reynolds number, between 100 and 1000, for flows over turbines of a single blade. In general, the results presented guarantee, with reliability and physical coherence, the applicability of the methodology in two-dimensional flows of this type.